Enzymatic Remediation of Polyethylene Terephthalate (PET)–Based Polymers for Effective Management of Plastic Wastes: An Overview - Maurya, Ankita; Bhattacharya, Amrik; Khare, Sunil Kumar (Frontiers in Bioengineering and Biotechnology, 2020)
Globally plastic-based pollution is now recognized as one of the serious threats to the environment. Among different plastics, polyethylene terephthalate (PET) occupies a pivotal place, its excess presence as a waste is a major environmental concern. Mechanical, thermal, and chemical-based treatments are generally used to manage PET pollution. However, these methods are usually expensive or generate secondary pollutants. Hence there is a need for a cost-effective and environment-friendly method for efficient management of PET-based plastic wastes. Considering this, enzymatic treatment or recycling is one of the important methods to curve PET pollution. In this regard, PET hydrolases have been explored for the treatment of PET wastes. These enzymes act on PET and end its breakdown into monomeric units and subsequently results in loss of weight. However, various factors, specifically PET crystallinity, temperature, pH are known to affect this enzymatic process. For effective hydrolysis of PET, high temperature is required, which facilitates easy accessibility of substrate (PET) to enzymes. However, to function at this high temperature, there is a requirement of thermostable enzymes. The thermostability could be enhanced using glycosylation, immobilization, and enzyme engineering. Furthermore, the use of surfactants, additives like Ca2+, Mg2+, and hydrophobins (cysteine-rich proteins) have also been reported to enhance the enzymatic PET hydrolysis through facilitating easy accessibility of PET polymers. The present review encompasses a brief overview of the use of enzymes towards the management of PET wastes. Various methods affecting the treatment process and different constrain arising thereof are also systematically highlighted in the review.